Pengembangan Media Pembelajaran Berbasis Video pada Teori Pemesinan Frais - Muhammad Aziz Fauzan; Dwi Rahdiyanta (Department of Mechanical Engineering Education, 2017)
This research is intended to produce a suitable video-based learning media on the making of helical gear in Milling Theory. This is a Research and Development type research incorporating six steps, namely: stating the potentials and problems, collecting data, designing the product, validation of the product design, revision of the design and product trials. Feasibility of the learning media was assesed by content-expert, media expert, teachers and students, by means of questionnaires. The quantitative research data were analized using quantitative-descriptive analysis technique. The product of this research is a learning media in the form of mp4 videos about Milling Machining practice. The media includes introductory music, videos, naration and animation. The feasibility level of the video-based learning media were assessed and presented in the form of percentages and classifications. The content-expert gave a feasibility level of 96.50% with classification of